Management of acute cellular rejection after pediatric heart transplantation - Caitlin Milligan, MD, PhD; Kevin P. Daly, MD (JHLT Open)
Acute cellular rejection (ACR) remains a leading cause of allograft injury after pediatric heart transplantation and contributes to chronic graft dysfunction, cardiac allograft vasculopathy, antibody mediated rejection, and mortality post-transplant. Understanding the risks for developing ACR, with a focus on immunosuppression adherence, and applying appropriate screening methods is important to limit the impact of this complication. While endomyocardial biopsy remains the gold standard for diagnosis and classification of ACR, additional non-invasive screening methods can be used to stratify rejection risk and limit biopsies. These screening methods include the use of gene expression profiling, donor-derived cell-free DNA, echocardiography, and cardiac magnetic resonance imaging. Management of ACR depends on the severity of allograft injury; In cases of severe rejection, treatment includes corticosteroids, anti-thymocyte globulin, and hemodynamic support. This review highlights the impact of ACR on transplant outcomes and risk factors for ACR with a particular emphasis on screening, diagnosis, and management. Ultimately, continued improvement in prevention, earlier detection, and prompt treatment of ACR are important to enhance outcomes for pediatric heart transplant recipients.